Comparative performance analysis of Spring Boot and Quarkus frameworks in Java applications - Szymanek, Grzegorz; Smołka, Jakub (Journal of Computer Sciences Institute, 2025)
The paper presents comparative performance characterization of two Java application development frameworks, Spring Boot and Quarkus. A representative reference application was implemented using both frameworks to enable such a comparison. The study entailed measurements in terms of multiple metrics, including compilation time, initialization time for an application, final file sizes, CPU and RAM consumption, latency in HTTP response, throughput, and efficiency of database queries. Tests were run on both JAR and native image versions with varying loads. Results convincingly showed the benefits of native Quarkus in startup performance and resource utilization. Spring Boot is still a proven option with a broader tooling universe supporting it, though. This research gives interesting input to decide on the best technology for modern Java applications.